GROW Coaching as a Strategy to Enhance Personal Commitment in Professional Development a Literature Study - Tuti Herawati; Neila Aisha (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2026)
Professional development requires not only technical competence and increased knowledge, but also a strong personal commitment to achieving long-term goals. In various professional contexts, individuals often experience difficulties in maintaining consistency, motivation, and responsibility for their self-development and career. Therefore, an effective coaching approach is needed to strengthen individual commitment on an ongoing basis. This study aims to analyze the role of the GROW coaching model as a strategy in increasing personal commitment to professional development through a literature study approach. The study used a qualitative descriptive method with a narrative literature review approach through a review of various scientific journals, books, and academic publications related to GROW coaching, personal commitment, self-awareness, and professional development. The results of the study indicate that the GROW model, consisting of Goal, Reality, Options, and Will, contributes significantly to the formation of self-awareness, intrinsic motivation, a sense of responsibility, and ownership of personal goals. The "Will" stage in particular plays a crucial role in encouraging individuals to transform intentions into concrete actions and ongoing commitment. Furthermore, the literature shows that commitment tends to be stronger when solutions and action plans emerge from an individual's own awareness rather than from external direction. This study concludes that the GROW coaching model is not only a communication framework for coaching practice, but also a strategic development approach capable of strengthening personal commitment in professional and organizational contexts. This research also provides theoretical and practical implications for leadership, human resource development, education, and professional coaching practice